2013
DOI: 10.4081/ijas.2013.e20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Chinese Herbs on Growth Performance, Blood Antioxidant Function and Immunity Status in Holstein Dairy Heifers Fed High Fibre Diet

Abstract: Two experiments were carried out to investigate the effects of supplemental Chinese herbs, Fructus Ligustri Lucidi (FLL), Radix Astragali (RA) and Radix Codonopsis (RC) on growth performance, blood antioxidant and immune function in Holstein dairy heifers fed high fibre diet. Experiment 1 indicated that the supplementation of the three herbs had no effect on dry matter intake. FLL Supplementation increased heifers average daily gain (ADG), final body weight and feed efficiency. Experiment 2 indicated that FLL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The herbals contain polysaccharides, alkaloids, glycosides, etc., and have both nutritional and medicinal properties. Fructus Ligustri Lucidi, when supplemented to the ration, could increase heifers average daily gain (ADG), final body weight and feed efficiency, increase concentration of superoxide dismutase (SOD) and reduce concentration of malondialdehyde (MDA) to improve the blood antioxidant function, and reduce concentrations of prostaglandin E2 (PGE2) and immunoreactive fibronectin (IFN-γ) to improve immune function (Qiao et al, 2013). Mannan oligosaccharide and an essential oil blend could enhance performance and also increase eggshell weight as free radical scavengers (Bozkurt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The herbals contain polysaccharides, alkaloids, glycosides, etc., and have both nutritional and medicinal properties. Fructus Ligustri Lucidi, when supplemented to the ration, could increase heifers average daily gain (ADG), final body weight and feed efficiency, increase concentration of superoxide dismutase (SOD) and reduce concentration of malondialdehyde (MDA) to improve the blood antioxidant function, and reduce concentrations of prostaglandin E2 (PGE2) and immunoreactive fibronectin (IFN-γ) to improve immune function (Qiao et al, 2013). Mannan oligosaccharide and an essential oil blend could enhance performance and also increase eggshell weight as free radical scavengers (Bozkurt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of in vitro studies, Benchaar et al (2006) showed that digestibility of nutrients (N, ADF, NDF, DM, and OM) was not affected by different levels of herbs. Qiao et al (2013) demonstrated that adding Chinese herb resulted in improved digestibility of nutrients and performance of Holstein heifers. Herbal extracts and flavours, alone or in combination, may improve health and performance (Janssen et al 1987;Horton et al 1991;Bakhiet & Adam 1995;SkrabkaBlotnicka et al 1997;Gill 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on a number of secondary metabolites such as tannins, saponins and herbal extracts have shown their favourable impacts on fermentation in the rumen, digestibility of nutrients, and production performance of ewes and cattle (Lila et al 2003;Busquet et al 2006;Beauchemin et al 2007;Benchaar et al 2006Benchaar et al , 2008. Qiao et al (2013) added Chinese herbs to diets fed to Holstein cows to show improvements in antioxidant indices and immunity system; adding Chinese herbs resulted in increased concentration of IgG and interferon gamma compared to the control group. In a number of in vitro studies, Benchaar et al (2006) showed that digestibility of nutrients (N, ADF, NDF, DM, and OM) was not affected by different levels of herbs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al (2012) found that the addition of Astragalus polysaccharides to the diet increased the daily feed intake of lambs. Also, Qiao et al (2016) found that the addition of Chinese herbal medicine increased the average daily gain, nal body weight and feed conversion e ciency of Holstein dairy cows. The results of an experiment on the various levels of a Chinese herbal medicine complex on the growth performance of simulated Taiwan country chickens showed that the complex at 0.3% increased both average daily weight gain and feed conversion ratio (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Chinese herbal medicines are rich in nutrients and biologically active substances (Hossain et al, 2012). In addition to disease prevention, treatment, and enhancing the body's immunity, they can also improve feed conversion e ciency and promote animal growth and development (Qiao et al, 2016). Zhong et al (2012) found that the addition of Astragalus polysaccharides to the diet increased the daily feed intake of lambs.…”
Section: Discussionmentioning
confidence: 99%